Emlploynent creation and viability of rural enterprise projects: cases of laundry and tailoring in Khulna and Gopalganj - Matin, Rukhsana (BRAC, 2019)
This study aimed to assess the viability of t\vo rural enterprises, laundry and tailoring shop from both the organization and members' perspectives, using ratio analysis. The study also attempted to measure the extent of new employment generated. Results reveal that though both the projects hold potential for increasing employment and output, tailoring was more readily acceptable since it required lower working capital consistent with factor endowments and yielded higher rate of return. Besides, sufficient demand is a pre-requisite for realization of employment and output that are technically feasible. Age of member was found to be a significant factor in influencing the number of hours worked. The study suggests that sufficient emphasis must be given on training of the members as it affects the profitability of the enterprise.